Aplikasi Penilaian Lomba Burung Murai Batu Berbasis Android - Lucky Febrian; Buhori Muslim; Debi Gusmaliza (Training and Research Institute Jeramba Ilmu Sukses (TRI - JIS), 2021)
This research aims to design and build an Android-based Magpie Batu race evaluation app. The appraisal application is one of the media used in the judging process for judges to participants in the bird competition. Based on the results of observations on Saturday's cheerful contest. It was found that the current system was still manual using paper, pen and flag media to determine the results of the race and the process the calculation of the value after the end time is also still manually with counting the total number of values ​​obtained can only be known which bird won, so it was less effective in the assessment of the Magpie Stone race. The system development method in this application uses the Luther method which consists of several stages, namely concept, design, material collecting, assembly, testing, distribution. To measure the success of this application, alpha testing is done to test the validity of the product to design experts, material experts, linguists and media experts. The results expected in this study are in the form of an Android-based appraisal of the Magpie Stone contest as a media for the Magpie Stone race in Pagar Alam City.